Physical exercise is safe and feasible in thrombocytopenic patients with hematologic malignancies: a narrative review. Issue 1 (1st January 2020) - Morishita, Shinichiro; Nakano, Jiro; Fu, Jack B.; Tsuji, Tetsuya
ABSTRACT: Many studies have reported that physical exercise can improve the levels of function, quality of life (QoL), and fatigue in patients with hematologic malignancies. However, exercises should be prescribed with caution in patients with thrombocytopenia to prevent exercise-related bleeding. Some studies have suggested threshold platelet counts at which physical exercise can safely be performed. Herein, we review the current literature to determine the platelet count thresholds and types of physical exercise that may be prescribed to reduce the risk of exercise-related bleeding in those with hematological malignancies while undergoing chemotherapy.